Application of Statistical Experimental Design to Benzylation of p-Chlorophenol (Bangladesh Journal of Scientific and Industrial Research, 2010)
A 23 Yates pattern experimental design was used to develop a mathematical model for the benzylation of p-chlorophenol with benzyl alcohol in the presence of perchloric acid as catalyst. A set of trials was planned with two replicates and the centre point trial with 4 replicates according to the design. The critical response was the yield of 2-benzyl-4-chlorophenol. Main effects as well as two- and three- factor interaction effects were statistically significant. The highest experimental yield was 91.6%. The experimental settings were 130°C, molar ratio of p-chlorophenol to benzyl alcohol 4:1, amount of 60% perchloric acid 5% by wt. of p-chlorophenol, addition time 2 h and stirring time 1 h. The difference between the experimental and predicted yields did not exceed 0.04%.Key words: p-Chlorophenol; Benzyl alcohol; Perchloric acid; 2-benzyl-4-chlorophenol; Experimental design DOI: 10.3329/bjsir.v45i2.5706Bangladesh J. Sci. Ind. Res. 45(2), 105-110, 2010